Role of the N, N′-dimethylbiguanide metformin in the treatment of female prepuberal BALB/c mice hyperandrogenized with dehydroepiandrosterone - Sander, Valeria Analía (2006)
The present study investigated the role of the N, N{ 0 }-dimethylbiguanide metformin (50 mg/100 g body weight in 0.05 ml water, given orally with a canulla) in the prevention of endocrine and immune disorders provoked by the hyperandrogenization with dehydroepiandrosterone (DHEA) in prepuberal BALB/c mice. The treatment with DHEA (6 mg/100 g body weight in 0.1 ml oil) for 20 consecutive days, recreates a mouse model that resembles some aspects of the human polycystic ovary syndrome (PCOS). The treatment with DHEA did not modify either body mass index (BMI) or blood glucose levels, but did increase fasting insulin levels when compared with controls. Markers of ovarian function – serum estradiol (E), progesterone (P) and ovarian prostaglandin E (PGE) – were evaluated. The treatment with DHEA increased serum E and P levels while ovarian PGE diminished. When metformin was administered together with DHEA, serum insulin, E and P levels, and ovarian PGE values did not differ when compared with controls. Using flow cytometry assays we found that the treatment with DHEA diminished the percentage of the CD4 1 T lymphocyte population and increased the percentage of the CD8 1 T lymphocyte population from both ovarian tissue and retroperitoneal lymph nodes. However, when metformin was administered together with DHEA, the percentages of CD4 1 and CD8 1 T lymphocyte populations from both ovarian tissue and retroperitoneal lymph nodes were similar to those observed in controls. Finally, when DHEA was administered alone it increased the serum tumor necrosis factor-alpha (TNF-a) levels when compared with controls; however, when metformin was administered together with DHEA, serum TNF-a levels were similar to controls. These results indicate that metformin is able, directly or indirectly, to avoid the endocrine and immune alterations produced when mice are hyperandrogenized with DHEA.